Humpback Whale Movements and Behavior in Response to Whale-Watching Vessels in Juneau, AK - Schuler, Alicia R.; Piwetz, Sarah; Di Clemente, Jacopo; Steckler, David; Mueter, Franz; Pearson, Heidi C. (Frontiers in Marine Science, 2019)
The whale watching industry in Juneau, Alaska relies primarily on the presence of North Pacific humpback whales (Megaptera novaeangliae). To meet demands from the rapidly growing tourism industry, the number of whale watching vessels in this region has tripled over the last 18 years. As a result, increased vessel presence could have negative effects on humpback whales, ranging from short-term behavioral disturbance to long-term impacts. The current humpback whale viewing regulations are outdated and may not be as effective as they were 18 years ago, when both the whale watching industry and humpback whale population were smaller. The present study assessed how humpback whale movement and behavioral patterns were affected by (1) vessel presence and number of vessels present, and (2) time spent in the presence of vessels. The study also determined how humpback whale behavioral state transitions were affected by vessel presence. A total of 201 humpback whale focal follows were conducted during summer 2016 and 2017. Based on linear mixed effects models, whales in the presence (vs. absence) of vessels exhibited 38.9% higher deviation in linear movement (p = 0.001), 6.2% increase in swimming speed (p = 0.047) and a 6.7% decrease in inter-breath intervals (IBI) (p = 0.025). For each additional vessel present, deviation increased by 6.2% (p = 0.022) and IBI decreased by 3.4% (p = 0.001). As time spent in the presence of vessels increased, respiration rate increased (p = 0.011). Feeding and traveling humpback whales were likely to maintain their behavioral state regardless of vessel presence, while surface active humpback whales were likely to transition to traveling in the presence of vessels. These short-term changes in movement and behavior in response to whale watching vessels could lead to cumulative, long-term consequences, negatively impacting the health and predictability of the resource on which the industry relies. Current formal vessel approach regulations and voluntary guidelines should be revisited to reduce vessel pressure and mitigate potential negative effects of this growing whale watching industry.